The Structure of Betrayal: Trade Union Bureaucracy and Public Sector Struggles in British Columbia - Hurl, Chris (Studies in Political Economy, 2009)
Serving on the executive committee of CUPE 4163 at the University of Victoria and actively participating in the Victoria Communities Solidarity Coalition, I had the opportunity to experience these [public sector] struggles first hand. While I played only a marginal role (i.e., standing on picket lines, organizing discussion forums, and attending public meetings), I hope to contribute my perspective as a participant observer. This is not intended to be a detailed history; rather, I will draw on various interpretations of the struggles in BC to make a broader theoretical intervention in conceptualizing the defeat of the labour movement in the so-called “neoliberal era.” Viewing bureaucracy as an uneven field of struggle, I argue that the [Hospital Employees' Union] strike demonstrates the importance of distinguishing between different elements of BC’s labour leadership in challenging the provincial government’s denial of collective bargaining freedoms to public sector workers. --From introduction